The relationship between cavum septum pellucidum and psychopathic traits in a large forensic sample. (April 2018) - Crooks, Dana; Anderson, Nathaniel E.; Widdows, Matthew; Petseva, Nia; Koenigs, Michael; Pluto, Charles; Kiehl, Kent A.
Abstract: Cavum septum pellucidum (CSP) is a neuroanatomical variant of the septum pellucidum that is considered a marker for disrupted brain development. Several small sample studies have reported CSP to be related to disruptive behavior, persistent antisocial traits, and even psychopathy. However, no large-scale samples have comprehensively examined the relationship between CSP, psychopathic traits, and antisocial behavior in forensic samples. Here we test hypotheses about the presence of CSP and its relationship to psychopathic traits in incarcerated males ( N = 1432). We also examined the incidence of CSP in two non-incarcerated male control samples for comparison ( N = 208 and 125). Ethnic and racial composition was varied with a mean age of 33.1, and an average IQ of 96.96. CSP was evaluated via structural magnetic resonance imaging. CSP was measured by length (number of 1.0 mm slices) in continuous analyses, and classified as absent (0) or present (1+ mm), as well as by size (absent (0), small (1–3), medium (4–5), or large (6+ mm)) for comparison with prior work. The Wechsler Adult Intelligence Scale (WAIS-III), Structured Clinical Interview (SCID-I/P), and Hare Psychopathy Checklist-Revised (PCL-R) were used to assess IQ, substance dependence, and psychopathy, respectively. CSP length was positively associated with PCL-R total, Factor 1 (interpersonal/affective) and Facets 1 (interpersonal) and 2 (affective). CSP was no more prevalent among inmates than among non-incarcerated controls, with similar distributions of size. These results support the hypotheses that abnormal septal/limbic development may contribute to dimensional affective/interpersonal traits of psychopathy, but CSP is not closely associated with antisocial behavior, per se. Highlights: Small CSP is common in both incarcerated and non-incarcerated individuals. CSP size is related to the interpersonal /affective elements of psychopathy. CSP size is not distinguishing of severity of antisocial behavior.